Phenotypic and genotypic characterization of carbapenemases of Gram-negative bacilli isolated in bronchial aspirates in a public hospital of Santa Elena in times of COVID-19 - Suarez Gonzalez, Patricia Del Pilar; Lascano-Espinoza, Carmen Obdulia; Jarrin-Beltrán, Carlos; Hernández Ortiz, Adonis Faustino; Borbor Paltín, Gino Arturo (Kasmera, 2025)
During the COVID-19 pandemic, the emergence of highly antibiotic-resistant microorganisms has been documented, highlighting carbapenemase-producing organisms, which confer resistance to carbapenems and other antimicrobials. This work aimed to characterize, phenotypically and genotypically, carbapenemases (bla KPC, bla VIM, bla IMP-1, bla NDM and bla  OXA-48) produced by clinical isolates of Gram-negative bacilli isolated from bronchial aspirates from in-patientes at the intensive care unit in a public hospital in Santa Elena (Ecuador) over a two-year period (april 2020 - april 2022). In this period, strains of A. baumannii Complex (41.41%; n=41), K. pneumoniae (21.21%; n=21) and P. aeruginosa (4.04%; n=4) were mainly detected.  In 13 strains of K. pneumoniae, the bla KPC (61,90%), in 3 bla NDM (14,29%) and in 1 bla VIM (4,76%) genes were found. In the isolates of A. baumannii Complex, strains producing bla IMP-1 (2,44%) and bla NDM (2,44%). In an isolate of P. aeruginosa, the gene bla VIM (50,00%) was identified. Rapid and accurate identification of carbapenemases provides epidemiological information relevant to antimicrobial therapy, infection control, and prevention of widespread spread